Analysis of Mercury Heavy Metal Content in Snakehead, Tilapia and Catfish from Taliwang Lake - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati; Sedijani, Prapti (Jurnal Biologi Tropis, 2026)
Research on heavy metals in fish is essential. This study aimed to determine the levels of the heavy metal mercury (Hg) in Snakehead (Channa striata), Catfish (Clarias batrachus), and Mozambique Tilapia (Oreochromis mosambicus) sampled from Lake Taliwang. The study is particularly valuable for protecting consumers from heavy metal contamination associated with fish consumption. The research was conducted at Lake Taliwang, West Sumbawa, with two observation stations established: one in the eastern section and one in the western section of the lake. The three fish species were caught using gill nets, with four samples collected for each species at each station. Each fish sample was placed in a plastic bag and stored in a sample storage box. The samples were subsequently analyzed at the West Nusa Tenggara Health Testing and Calibration Laboratory. Data analysis involved extracting fish muscle tissue and determining Hg content using a Mercury Analyzer. The wet digestion stage of the sample preparation process involved decomposing organic matter within the samples using strong acids specifically HNO3 and H2O2 as digesting agents. The data obtained represent Hg levels in mg/kg or ppm (parts per million). The final step involved descriptive processing of the obtained Hg concentrations and presenting the results in tabular form, based on the Mercury Analyzer findings. The study concluded that the Hg content in Snakehead (Channa striata), Catfish (Clarias batrachus), and Mozambique Tilapia (Oreochromis mosambicus) from Lake Taliwang ranged from 0.04 to 0.09 mg/kg.